Pattern and Causes of Extractions of Permanent Teeth in Tertiary Care Hospitals in Karachi, Pakistan (Medical Forum Monthly, 2023)
ABSTRACTObjective: To investigate the causes of dental extractions of permanent teeth in flood victims receiving treatment in tertiary care hospitals.Study Design: Descriptive observational study.Place and Duration of Study: This study was conducted at the Two Tertiary Dental Hospitals of Karachi from mid-January to mid-March 2023.Materials and Methods: The current study investigated the causes of dental extractions of permanent teeth in 211 patients. Participants of this study were 10 to 70 years old. A specific survey form was used to collect information from the patients. SPSS version 27 was used for statistical analyses.Results: The highest number of extracted teeth was reported in 21-30 years old females. Dental caries (49.3%) was the leading cause of extraction followed by periodontal problems (22.3%). The most common teeth that required extractions were mandibular third molars (19.4%) followed by mandibular first molars (16.4%).Conclusion: Dental caries was reported to be the most prevalent cause of extractions of permanent teeth in flood-affected individuals.